Gastrointestinal Parasitic Infestation of Naemorhedus goral in Tattakuti Wildlife Sanctuary, Jammu and Kashmir - Bhat, Rouf Ahmad; Tak, Hidayatullah; Bhat, Bilal A.; Fazili, Mustahson F.; Wani, Hameem Mushtaq; Ahmad, Riyaz (Indian Forester, 2021)
For assessing and managing risk of parasitic infection in threatened wildlife species, it is important to have a baseline information on this lesser studied aspect. The current study, a step to investigate the presence and prevalence of different gastrointestinal parasites in Himalayan goral (Naemorhedus goral) was initiated with systematic collection of 57freshfaecal samples from different areas of the Tattakuti Wildlife Sanctuary. The samples were processed by the standard sedimentation and floatation techniques. A total of eight parasite species including five nematodes, one cestode, one trematode and one protozoan were recorded. Most of the positive samples were infected with mixed infection of two or more parasites. The most prevalent parasite was Eimeria spp. (49.12%), followed by Haemonchus contortus (33.33%), Trichuris ovis (29.82%), Nematodirus spp. (29.82%), Strongyloides papillosus (28.07%), Trichostrongylus spp. (26.31%), Fasciola hepatica (19.29%), and Moniezia expensa (17.54%). The high parasite prevalence might have an adverse effect on the health of this near threatened goat species. The possibility of cross-transmission between livestock and wild ungulates of this sanctuary is under investigation as the sanctuary receives thousands of livestock during summer.